Open Ended Problems Learning Model in Learning Poetry Writing Skills for Vocational School Students - Vera Sardila; Yesi Mandala Putri; Welli Marlisa; Rolli Gautama; Anggi Rosita Dewi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to describe the implementation of the Open Ended Problems learning model in teaching poetry writing skills to tenth-grade students of vocational school especially at SMKIT Al-Izhar School Pekanbaru. This research employed a qualitative descriptive method involving 43 students as the research subjects. The data were collected through observation, documentation, and assessment of students’ poetry works. The results showed that the implementation of the Open Ended Problems learning model was able to support students’ creativity in writing poetry. This was reflected in the students’ achievement in the aspects of theme and meaning originality, strength of imagination, diction accuracy, as well as the use of figurative language and imagery, which generally fell into the good category with an average score of 86.16.